A review on research of fire-induced progressive collapse on structures. (15th July 2021) - M., Vishal; K.S., Satyanarayanan
Abstract : Purpose: This paper delineates a literature review on fire-induced progressive collapse on structures and the effect of high temperature on structures and elements. After the occurrences of fire in the World Trade Center in the USA, the researchers started concentrating on the progressive collapse that happens due to high temperature. Currently, most of the researchers are working on fire-induced progressive collapse on structures using high-temperature behavior on materials which are used for construction. The researchers have been doing an intensive study to find a better strategy to prevent the building from structural fire damage or collapse with available codes and guidelines throughout the world. This paper aims to provide a better understanding and analytical solutions on the basis of the recent works done by researchers in fire-induced progressive collapse and methods adopted to find the collapse mechanism. Design/methodology/approach: This paper is written by studying different literature papers of 109 related to progressive collapse on structures and fire-induced progressive collapse. Findings: The behavior of structures due to high temperature and collapse conditions due to fire in different scenarios is identified. Originality/value: This paper fulfills an identified need to study how the structure can withstand high-temperature conditions in our day-to-day lives.